INTEGRATED ASSESSMENT OF THE RUSSIAN ECONOMY COMPETITIVENESS - Kotenkova, Svetlana; Varlamova, Julia; Larionova, Natalia; Rudaleva, Irina (Gênero & Direito, 2019)
In the context of the modern economic processes development at the regional level, such an aspect as regional competitiveness plays an extremely important role. To quantify the competitiveness of the regions of the Russian Federation, 10 subjects were taken. A comparative analysis was carried out on the basis of 35 indicators divided into 7 blocks depending on factor affiliation. The result of the analysis is the ranking of the considered regions of the Russian Federation in terms of competitiveness.The quantitative analysis carried out in conjunction with a qualitative assessment based on the SWOT analysis allows us to create a relatively clear picture of the competitiveness ratio of individual Russian regions, the main characteristic of which is their rather strong differentiation, due to the geoeconomic features already mentioned above. One can use the successful experience of countries such as Canada, China and Ireland in the formation of directions considered in this paper for increasing the competitiveness of regions.